Peningkatkan kemampuan guru dalam penyusunan proposal penelitian tindakan kelas bagi Guru SD Perumnas 1 Kota Kupang - Fembriani, Fembriani; Ga, Paulina Riwu; Kota, Martha K (Nur Science Institute, 2022)
The workshop training objectives are to improve teachers' ability to prepare proposals and classroom action research (CAR). This activity was carried out in SD Perumnas 1 Kupang City. This training is expected to benefit teachers, especially teachers, to be more motivated in conducting classroom action research. In addition, this training is used to develop and improve the quality of learning by using one of the methods, models, approaches, and related learning strategies to achieve the expected learning outcomes. CAR is beneficial for teachers to improve the quality of the process and learning outcomes in the classroom. By carrying out the CAR stages, teachers can find solutions to problems that arise in their class, not someone else's, by applying various creatively relevant theories and learning techniques. In addition, to applied research, besides the teacher carrying out his primary task of teaching in the classroom, there is no need to leave the students. So CAR is research that raises the actual problems teachers face in the field. By implementing CAR, the teacher has a dual role: practitioner and researcher.